ChemInform Abstract: Asymmetric Domino Aza‐Michael Addition/[3 + 2] Cycloaddition Reactions as a Versatile Approach to α, β, γ‐Triamino Acid Derivatives. Issue 31 (5th August 2014) - Kapras, Vojtech; Pohl, Radek; Cisarova, Ivana; Jahn, Ullrich
Abstract Nonaflyl azide serves as an effective diazo transfer reagent forming a link between the conjugate addition and cycloaddition steps.